The effectiveness of dexamethasone as a combination therapy for COVID-19 - Namazi Nader (Acta Pharmaceutica)
Coronavirus disease 2019 (COVID-19) was reported as a global pandemic in March 2020 after invading many countries and leaving behind tens of thousands of infected patients in a brief time span. Approval of a few vaccines has been obtained and their efficacy of varying degrees established. Still, there is no effective pharmaceutical agent for the treatment of COVID-19 though several drugs are undergoing clinical trials. Recent studies have shown that dexamethasone, a corticosteroid, can reduce the rate of COVID-19-related mortality in the intensive care unit by 35 % for patients who are on mechanical ventilation. Although variable efficacy of other combination therapies has been reported for treating COVID-19 associated with acute respiratory distress syndrome (ARDS), dexamethasone is an extensively used drug in many treatment regimens against COVID-19. The current review aims to explore the role of dexamethasone as an efficient combination treatment for COVID-19.